Kernel regression coefficients for practical significance - Vinod, Hrishikesh D (Journal of risk and financial management, 2022)
Quantitative researchers often use Student's t-test (and its p-values) to claim that a particular regressor is important (statistically significantly) for explaining the variation in a response variable. A study is subject to the p-hacking problem when its author relies too much on formal statistical significance while ignoring the size of what is at stake. We suggest reporting estimates using nonlinear kernel regressions and the standardization of all variables to avoid p-hacking. We are filling an essential gap in the literature because p-hacking-related papers do not even mention kernel regressions or standardization. Although our methods have general applicability in all sciences, our illustrations refer to risk management for a cross-section of firms and financial management in macroeconomic time series. We estimate nonlinear, nonparametric kernel regressions for both examples to illustrate the computation of scale-free generalized partial correlation coefficients (GPCCs). We suggest supplementing the usual p-values by 'practical significance' revealed by scale-free GPCCs. We show that GPCCs also yield new pseudo regression coefficients to measure each regressor's relative (nonlinear) contribution in a kernel regression.